2017
DOI: 10.1590/1678-457x.24716
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of tropical fruit juice based on sensory and nutritional characteristics

Abstract: The objective of this study was, through mixing design and response surface methodology, to optimize a reduced calorie mixed juice of persimmon, orange and pineapple based the sensory and nutritional characteristics. This study also aimed to carry out the survey of the physicochemical characteristics that are desirable in this product. It was found that juice of these fruits, when combined, have better sensory and nutritional characteristics than when isolated. The consumer has a preference for mixed fruit jui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
7
19
0
3
Order By: Relevance
“…Generally, as that of sensory acceptance, the combination of vegetable-fruit helps to develop juices which are nutritionally superior to those prepared with single fruits/ vegetables (Curi et al 2017). AGJ and BGJ beverages as well aligned with the previous report and found to be rich in phenolics such as anthocyanins.…”
Section: Phenolic Content and Anthocyaninssupporting
confidence: 81%
See 1 more Smart Citation
“…Generally, as that of sensory acceptance, the combination of vegetable-fruit helps to develop juices which are nutritionally superior to those prepared with single fruits/ vegetables (Curi et al 2017). AGJ and BGJ beverages as well aligned with the previous report and found to be rich in phenolics such as anthocyanins.…”
Section: Phenolic Content and Anthocyaninssupporting
confidence: 81%
“…This will enhance the shelf-life as well as the aesthetic properties of the beverage. Further, various studies showed that blending enhances the sensory as well as the nutritional quality of the beverages (Curi et al 2017). Therefore, it is important to study the characteristics of the blended beverages and their optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Sugars are one of the most important constituents of fruit products. They are an essential for flavor, acting as a natural food preservative (Curi et al., 2017). The reducing sugar content of all jujube beverages was increased significantly ( p < .05) after 4 months of the storage (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Bahan lainnya yaitu air minum, gula kristal putih, SCOBY kombucha. Alat yang digunakan untuk analisis fisikokimia meliputi refractometer (ATAGO Master) skala 0-32%, piknometer 10 mL (IWAKI), Ostwald viscometer, colour reader minolta CR10 (Konica Minolta Sensing) (Curi et al, 2017).…”
Section: Bahan Dan Metode Bahanunclassified
“…Kombucha cascara dianalisis sifat fisiknya yang meliputi total padatan terlarut (Bayu et al, 2017), berat jenis (Azizah et al, 2012), viskositas dengan menggunakan metode ostwald (Bayu et al, 2017), warna dengan menggunakan alat colour reader (Curi et al, 2017). Sifat kimia kombucha cascara yang diukur meliputi nilai keasamannya dengan menggunakan pH meter (Chakravorty et al, 2016), total asam tertitrasi (Bhusari et al, 2013) Howard et al (2012) bahwa jumlah panelis tidak terlatih (untrained) minimal 75 orang, panelis terlatih (trained) minimal sebanyak 10 orang dan panelis ahli (expert) minimal sebanyak 6 orang.…”
Section: Analisis Fisik Dan Kimia Kombucha Cascaraunclassified